Risky and aggressive driving in young adults: Personality matters - Constantinou, Elena; Panayiotou, Georgia; Konstantinou, Nikos; Loutsiou-Ladd, Anthi; Kapardis, Andreas (My University, 2011)
Young, novice drivers constitute a disproportionate percentage of fatalities and injuries in road traffic accidents around the world. This study, attempts to identify motivational factors behind risky driving behavior, and examines the role of personality, especially sensation seeking, impulsivity and sensitivity to punishment/reward in predicting negative driving outcomes (accident involvement and traffic offences) among young drivers. Gender and driver's age are additional factors examined in relation to driving outcomes and personality. Adopting the contextual mediated model of traffic accident involvement (Sümer, 2003), the study is based on the theory that personality, age and gender represent distal factors that predict accident involvement indirectly through their relationship with stable tendencies towards aberrant driving behavior. Results from correlations and Structural Equation Modeling using AMOS 6 indicated that direct personality effects on driving outcomes were few, whereas personality had significant correlations with aberrant driving behavior, showing that personality is a distal but important predictor of negative driving outcomes. These high risk traits appear to be at a peak among young male drivers. Thus, personality is important in understanding aggressive and risky driving by young adults and needs to be taken into consideration in designing targeted accident prevention policies.
Keywords: Driving; Impulsivity; Inhibition; Sensation seeking; Traffic accidents